Plant Functions in Wetland and Aquatic Systems: Influence of Intensity and Capacity of Soil Reduction - R.D. DeLaune; S.R. Pezeshki (The Scientific World Journal)
Wetland or hydric soils, in addition to excess water and limited air-filled porosity, are characterized by anaerobic or reducing conditions. Wetland plants have developed physiological and morphological adaptations for growing under these conditions. Various methods exist for measuring plant responses to reducing conditions in wetland and aquatic environments, including assessment of radial oxygen transport, cellular enzymatic transformations, changes in root structure, and nutrient uptake. However, a gap exists in quantifying the chemical properties and reducing nature of soil environment in which plant roots are grown. The variation in reducing conditions, oxygen demand, and other associated processes that occur in wetland soils makes it difficult to truly compare the plant responses reported in the literature. This review emphasizes soil-plant interactions in wetlands, drawing attention to the importance of quantifying the intensity and capacity of reduction and/or oxygen demand in wetland soils to allow proper evaluation of wetland plant responses to such conditions.